How milk gets from breast to baby - Jamani, Nurjasmine Aida (2014)
In normal breastfeeding, there are 2 elements necessary for getting milk from the breast to the baby : 1.A breast that produces and releases milk 2.A baby who is able to remove the milk from the breast with effective suckling